2020
DOI: 10.1109/access.2020.3008000
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Learning Algorithm in Feature Mining and Rapid Identification of Colorectal Image

Abstract: Based on deep learning technology, this paper proposes a two-stage colorectal image feature mining and fast recognition model to achieve fully automatic medical image pathology discrimination. Drawing on the ideas of multi-factor Meta-regression analysis widely used in the medical field and the model aggregation framework based on Bayesian prior probability theory, a prognostic model of colorectal tumors suitable for various situations and scenarios is constructed. And using a combination of public data sets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…According to study data, by 2030, there will be more than 2.2 million new colon cancer cases in the world [ 2 ], including more than 1.1 million deaths [ 1 ]. Some medical researches showed that the liver was the most prone organ for colorectal cancer to produce hematogenous metastasis [ 3 , 4 ]. Therefore, the discovery of CRLM biomarkers was useful for the diagnosis and targeting of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…According to study data, by 2030, there will be more than 2.2 million new colon cancer cases in the world [ 2 ], including more than 1.1 million deaths [ 1 ]. Some medical researches showed that the liver was the most prone organ for colorectal cancer to produce hematogenous metastasis [ 3 , 4 ]. Therefore, the discovery of CRLM biomarkers was useful for the diagnosis and targeting of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant data, more than 2.2 million new cases of colon cancer are expected to occur globally by 2030, including more than 1.1 million deaths [2,3]. According to some authoritative medical data, liver is the target organ that is most likely to produce blood metastasis in colorectal cancer [4,5].Therefore, the treatment of liver metastasis in colorectal cancer is one of the key and di cult points in current medical technology.16% 26% of colorectal cancer patients had liver metastases at the time of diagnosis, and 14%~24% of patients had liver metastases after primary radical resection [6][7][8][9]. Most patients with liver metastases were unable to undergo radical resection.…”
Section: Introductionmentioning
confidence: 99%